PENGEMBANGAN VIRTUAL CHEMISTRY LABORATORY SEBAGAI MEDIA PEMBELAJARAN BERBASIS EKSPERIMEN PADA MATERI KESETIMBANGAN KIMIA - Dheane Fadillah; Wiwit Alwi; Elvinawati (ALOTROP, 2026)
This research is the development of learning media in the form of a Virtual Chemistry Laboratory on chemical equilibrium material which aims to determine the level of media feasibility, student responses, and improvement of learning outcomes. Media development uses the 4D model (define, design, develop, and disseminate), but the research is limited to the development stage. Small-scale trials involved 15 students of class XII.D, while large-scale trials involved 35 students of class XI.A at SMAN 6 Bengkulu City. Data collection was carried out using interview sheets, needs questionnaires, validation sheets, student response questionnaires, and pretest and posttest instruments. The results of the feasibility test obtained a percentage of 86.39% in the material aspect and 89.72% in the media aspect with a very feasible category. Student responses obtained a percentage of 84.2% in the small-scale trial and 87.16% in the large-scale trial, with a very good category. The N-Gain value of 0.70 is included in the high category. Based on the research results, it can be concluded that the Virtual Chemistry Laboratory on chemical equilibrium material is very suitable for use in learning and is effective in improving student learning outcomes.